2016
DOI: 10.5545/sv-jme.2016.3523
|View full text |Cite
|
Sign up to set email alerts
|

Chip Formation Mechanism Using Finite Element Simulation

Abstract: Prediction of chip form produced during machining process is an important work when considering workpiece surface creation and possible damage caused by chips generated during machining. The paper presents a set of new results of cutting chip formation from the latest finite element method (FEM) model development. Generally, three types of chips (continuous, serrated, and discontinuous chips) are generated during metal machining. The formation of these three types of chips is investigated in relation to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The rheological behavior of machined materials in finite element models is usually described by the Johnson-Cook material model, which allows to consider the properties of workable material as a function depending not only on strain and strain-rate, but also on temperature. However, studies have shown [15] that for the modeling of different forms of chip in the process of cutting, it is necessary to use the Johnson-Cook progressive damage model in conjunction with the Johnson-Cook constitutive material model by using fracture energy as a damage evolution criterion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheological behavior of machined materials in finite element models is usually described by the Johnson-Cook material model, which allows to consider the properties of workable material as a function depending not only on strain and strain-rate, but also on temperature. However, studies have shown [15] that for the modeling of different forms of chip in the process of cutting, it is necessary to use the Johnson-Cook progressive damage model in conjunction with the Johnson-Cook constitutive material model by using fracture energy as a damage evolution criterion.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, FEM has become the main tool for simulating metal cutting processes. It provides appropriate approach to visualize cutting process, because it allows to predict various characteristics of the metal cutting such as cutting forces, temperatures, stresses, chip types and shapes, etc [1,6,15,22].…”
Section: Introductionmentioning
confidence: 99%
“…Chip morphology can be mainly divided into band-shaped, sawtooth-shaped and nodular chips. Chip formation reported by Mabrouki et al [45] Ozcatalbas et al [46], Dabade and Joshi et al [47,48], Opoz and Chen [39] that it is a combined crumbling/fracture/rupturing process with increasing shear plane angle; however, the partial shearing and tearing along shear plane reported in the work of Joshi et al 1999 [48].…”
Section: Sawtooth Chip Formation Mechanism Of Sicp/al Compositesmentioning
confidence: 95%
“…In this study, the cutting force and chip formation behavior in machining of SiCp/Al containing 50% vol of SiC reinforced particles and 10 μm size was defined along with different machining parameters. In the cutting process, chip formation or chip removal mechanisms play a vital role to understand the machinability characters [39]. The patterns and types of chips in chip formation mechanisms in SiCp/Al material give clues to understand the effect of machining parameters surface quality as well as the influences on the cutting force generation patterns.…”
Section: Effect Of Cutting Parameters On Chip Geometrymentioning
confidence: 99%
“…Above results clearly indicate the effectiveness of HPC in reducing the temperature. This is endorsed to a higher rate of conversion of mechanical to thermal energy by the chip evolution by shearing of solid material [16].…”
Section: A Effect Of High Pressure Coolant On Machining Temperaturementioning
confidence: 99%